Effect of a communication robot in the prevention of postoperative delirium in older persons: A randomized controlled trial - Koubun Imai (PLoS ONE, 2025)
As studies have reported reduced delirium in hospitalized older individuals with dementia who interacted with the seal-shaped robot “PARO,” the role of communication robots in preventing delirium was investigated. This study included patients aged ≥70 years who were hospitalized for surgery requiring general anesthesia. The patients were randomly assigned to either the control group (patients received regular delirium countermeasures using a team approach; n = 76) or the intervention group (patients received regular delirium countermeasures plus an intervention with the “BOCCO emo LTE” communication robot; n = 74). Delirium was diagnosed using the Intensive Care Delirium Screening Checklist. From admission until discharge, nurses recorded the presence or absence of delirium each day. Chi-square and Mann–Whitney U tests were conducted to examine intergroup differences in delirium incidence between the groups. Of the 150 patients who provided consent for participation, 18 developed delirium. Significantly fewer patients in the intervention group (4 patients) developed delirium compared to those in the control group (14 patients) (p = 0.014). Patients with delirium were more likely to be older (p = 0.036) and have dementia (p < 0.001), a history of delirium (p = 0.004), and a history of benzodiazepine use (p = 0.028) compared to those who did not have postoperative delirium. The results suggest that communication robots can effectively reduce delirium incidence. Additional studies with larger cohorts are needed to mitigate the influence of varying risk factor frequencies between groups, improve the assessment of delirium, and validate the current study’s findings. Trial registration Japan Clinical Trials Registry (jRCT) (URL: https://jrct.mhlw.go.jp; No. jRCT1030250018; date: April 1, 2025; retrospectively registered)